The Influence of Patient Numbers, Working Hours, and Length of Service on Hospital Nurses’ Fatigue Levels in the Inpatient Unit - Atika Aziza; Jovan Amadeo Muliyanto; Michael Reinard Reinard; Betshebha Ipung (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
Workload and working hours are critical factors in evaluating workforce effectiveness, particularly in healthcare settings. Nurse fatigue can adversely affect performance and professionalism, as reflected in decreased concentration, alertness, and overall work efficiency in hospital environments. This study aims to examine the relationship between burnout levels and the number of patients handled, working hours, and length of employment among nurses. A quantitative approach was employed using an analytical survey with a cross-sectional design. Data were collected using the Maslach Burnout Inventory–General Survey and analyzed through Spearman correlation tests. The findings indicate that all respondents experienced burnout symptoms with varying levels of severity. Further analysis reveals a significant negative relationship between burnout levels and both age and length of employment. At the dimensional level, emotional exhaustion and depersonalization are negatively associated with length of employment, while depersonalization also shows a negative correlation with age. These findings suggest that work experience and individual maturity play an important role in mitigating burnout. Therefore, adaptive workload management and more balanced working hour arrangements are essential to maintain the performance and professionalism of healthcare workers.